Morbimortalidad materno fetal por ruptura uterina - Sanchez Torres, Lorena Geoconda (Machala : Universidad Técnica de Machala, 2024)
Introducción: The incidence of uterine rupture is 5.3 in 10,000 births globally and 3 in 10,000 in developed countries. In the official document of the maternal death gazette of Ecuador in 2018, week 52, of the 17 pregnancies that ended in abortion, emphatically only 1 case was due to uterine rupture. Similarly, among the 23 cases involving obstetric hemorrhage, only 1 was caused by uterine rupture. Development: Uterine rupture is a rare, life-threatening peripartum complication with potentially serious consequences for the mother and fetus. Physiopathologically, it occurs due to the complete division of the three layers of the uterus, both the endometrium, myometrium and perimetrium during pregnancy or childbirth, it can be divided into incomplete and complete rupture depending on the degree, so that it can lead to the death of not being diagnosed in time. Conclusion: The current rate of elective cesarean sections worldwide is 21.1% and ranges between 5% in Africa and 42.8% in Latin America, leading to a greater number of complications secondary to a scarred uterus, including the dreaded uterine rupture. Access to statistical data in developing countries is limited, however, in Ecuador, the result of cases of uterine rupture obtained an incidence of around 5.9/10,000.
Introducción: La incidencia de la ruptura uterina es de 5.3 en 10.000 partos a nivel global y 3 en 10.000 en los países desarrollados. En el documento oficial de la gaceta de muerte materna del Ecuador en el año 2018, semana 52, de los 17 embarazos que terminaron en aborto enfáticamente solo 1 caso fue por ruptura uterina. De manera similar, dentro de los 23 casos que suponen hemorragia obstétrica, solo 1 fue causado por ruptura uterina. Desarrollo: La ruptura uterina es una rara complicación periparto que pone en peligro la vida y tiene consecuencias potencialmente graves para la madre y el feto. Fisiopatológicamente, se da por la completa división de las tres capas del útero, tanto el endometrio, miometrio y perimetrio durante el embarazo o el parto, se puede dividir en ruptura incompleta y completa según el grado, de manera que puede conllevar a la muerte de no ser diagnosticada a tiempo. Conclusión: La tasa actual de cesáreas electivas a nivel mundial es del 21,1% y oscila entre el 5% en el África y el 42,8% en América Latina, conlleva a un mayor número complicaciones secundarias a un útero con cicatrices, incluida la temida ruptura uterina. El acceso a los datos estadísticos en países en proceso de desarrollo es limitado, sin embargo, en Ecuador, el resultado de casos de ruptura uterina obtuvo una incidencia de alrededor de 5.9/10000.
Keywords: RUPTURA UTERINA; MORBIMORTALIDAD MATERNOFETAL; COMPLICACIONES OBSTETRICAS; CESAREA